2009
DOI: 10.1016/j.trstmh.2009.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Infection control education: Impact on ventilator-associated pneumonia rates in a public sector intensive care unit in Pakistan

Abstract: We describe efforts towards introducing infection control (IC) practices and establishment of antimicrobial resistance (AMR) surveillance in a public sector hospital in Pakistan. The study was conducted in an eight-bed intensive care unit. IC principles, introduced through interactive sessions, were used as an intervention and their impact was observed by conducting surveillance for ventilator-associated pneumonia (VAP) before and after the intervention. Respiratory isolates of VAP patients in the period after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 25 publications
2
22
0
1
Order By: Relevance
“…19e22,24,25 By contrast, Khan et al reported no statistically significant reduction in the overall VAP rates. 23 The mean duration of hospital stay decreased significantly in Apisarnthanarak et al's study (P < 0.001), in line with that of Khan et al, who found that the mean length of stay of nosocomially infected patients was significantly higher than that of uninfected patients (P < 0.001). 20,23 Monthly antibiotic and hospitalization costs were reduced significantly (P < 0.001) in Apisarnthanarak et al's study.…”
Section: Clinical Outcomessupporting
confidence: 82%
See 1 more Smart Citation
“…19e22,24,25 By contrast, Khan et al reported no statistically significant reduction in the overall VAP rates. 23 The mean duration of hospital stay decreased significantly in Apisarnthanarak et al's study (P < 0.001), in line with that of Khan et al, who found that the mean length of stay of nosocomially infected patients was significantly higher than that of uninfected patients (P < 0.001). 20,23 Monthly antibiotic and hospitalization costs were reduced significantly (P < 0.001) in Apisarnthanarak et al's study.…”
Section: Clinical Outcomessupporting
confidence: 82%
“…23 The mean duration of hospital stay decreased significantly in Apisarnthanarak et al's study (P < 0.001), in line with that of Khan et al, who found that the mean length of stay of nosocomially infected patients was significantly higher than that of uninfected patients (P < 0.001). 20,23 Monthly antibiotic and hospitalization costs were reduced significantly (P < 0.001) in Apisarnthanarak et al's study. 20 However, no statistically significant changes in the length of ICU and hospital stays were found by Kulvatunyou et al 21 No statistically significant changes in the mortality rates were found by Apisarnthanarak et al and Kulvatunyou et al, by contrast with Danchaivijitr et al, who found that mortality decreased significantly from 12.3% to 8.7% (P < 0.001).…”
Section: Clinical Outcomessupporting
confidence: 82%
“…Many groups and scientific societies have provided prevention guidelines in the last 10 years [19-22]. Several guidelines recommend different measures to decrease the incidence of VAP, including training, which quickly reduces the incidence of VAP rates, although its long-term efficacy is limited [23,24]. …”
Section: Discussionmentioning
confidence: 99%
“…Four studies targeted only ICU nurses (Al‐Faouri et al, ; Danchaivijitr et al, ; Kulvatunyou et al, ; Raurell‐Torreda, ), while the remainder were mixed participants. Three targeted nurses and RTs (Apisarnthanarak et al, ; Babcock et al, ; Zack et al, ); four included nurses and medical officers (Bloos et al, ; Salahuddin et al, ;Wolthuis et al, ; Wolthuis et al, ); and one study included nurses, medical officers and allied health professionals (Khan et al, ).…”
Section: Resultsmentioning
confidence: 99%